BENCHMARKING INTERCULTURAL COMMUNICATION COMPETENCE ASSESSMENT TOOLS FOR ESP TEACHING - Candel-Mora, Miguel Ángel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In an international professional environment, knowledge of the language alone is not a guarantee of success, as a result, recent language research emphasizes the intercultural component of foreign language education, and the development of tools to assess intercultural communication competence (ICC) towards the design of courses and training material. ICC research has produced a wide range of frameworks of analysis and assessment models to measure interculturally successful behaviors, such as adaptation, appropriateness, and effectiveness of intercultural interactions. However, tools and instruments to assess intercultural communication competence vary depending on whether their focus is on language learning or on cultural aspects and international or intercultural differences, but with regard to foreign language for specific purposes teaching, these tools do not seem to take into consideration the specificity of the context of learners. Therefore, the objective of this paper is to propose a framework of analysis specifically targeted for ESP learners based on existing ICC assessment tools and instruments, with a twofold purpose: to assess learners’ awareness and to apply it towards ESP syllabus design, and thus align ICC assessment with teaching objectives. Resumen En un entorno profesional internacional, el conocimiento de la lengua únicamente no es garantía de éxito. Estudios recientes destacan el componente intercultural en la enseñanza de lenguas extranjeras, y el desarrollo de herramientas para evaluar la competencia comunicativa intercultural (CCI) con el fin de elaborar cursos y material didáctico. La investigación en CCI ha generado modelos basados en actitudes y competencias para evaluar conductas interculturalmente aceptables, como la adaptación, o idoneidad y eficacia en las interacciones interculturales. Sin embargo, los instrumentos para evaluar la CCI varían dependiendo de si están orientados al aprendizaje de lenguas o a aspectos culturales y diferencias internacionales. No obstante en el campo de la enseñanza de lenguas extranjeras, estos modelos no parecen tener en cuenta el contexto específico de los estudiantes. Por lo tanto, el objetivo de este trabajo es diseñar un marco de análisis partiendo de instrumentos de evaluación de CCI existentes dirigido específicamente a los alumnos de IFE, con una doble finalidad: evaluar el grado de concienciación de los alumnos y aplicarlos al diseño de programas IFE, y por tanto alinear la evaluación en competencia comunicativa intercultural con los objetivos de aprendizaje.